2014
DOI: 10.1080/03079457.2013.866212
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of subtype B avian metapneumoviruses using RT-PCR restriction endonuclease digestion indicates field circulation of vaccine-derived viruses in older turkeys

Abstract: Live vaccines predominantly control avian metapneumovirus (aMPV) infection in poultry flocks, but vaccine virus can be found for extended periods after application. The most frequently used aMPV vaccine in Italy, VCO3 subtype B, was shown to contain a unique Tru9I restriction endonuclease site within the amplicons produced by a commonly used aMPV diagnostic reverse transcriptase (RT)-nested polymerase chain reaction (PCR). Analysis of European and database logged subtype B aMPV sequences confirmed that the seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…However it has not been possible to know whether encountered disease has been caused by inadequately controlled 793B field viruses or persisting, and possibly unstable, vaccine viruses. This is in contrast with, for example, AMPV, another common virus affecting poultry worldwide, where the deduction of genetic vaccine markers has shown that live vaccine derived virus can persist on farms and cause disease [15][16][17][18]. While it should be possible to similarly identify markers for IBV vaccines, this has not to date been reported, probably due to the unavailability of the IBV vaccine progenitor viruses needed in the critical vaccine-progenitor sequence comparisons.…”
Section: Discussionmentioning
confidence: 94%
“…However it has not been possible to know whether encountered disease has been caused by inadequately controlled 793B field viruses or persisting, and possibly unstable, vaccine viruses. This is in contrast with, for example, AMPV, another common virus affecting poultry worldwide, where the deduction of genetic vaccine markers has shown that live vaccine derived virus can persist on farms and cause disease [15][16][17][18]. While it should be possible to similarly identify markers for IBV vaccines, this has not to date been reported, probably due to the unavailability of the IBV vaccine progenitor viruses needed in the critical vaccine-progenitor sequence comparisons.…”
Section: Discussionmentioning
confidence: 94%
“…Another two VC03 vaccine/progenitor marker positions (3210 and 3391) (Listorti et al, 2014) were also found indicating a greater certainty that the Egyptian viruses were indeed VC03 vaccine derived.…”
Section: Discussionmentioning
confidence: 87%
“…This G/A mutation at position 7 of the G gene (Fig. 5) was recently identified as a marker for the AVIFFA/VC03 vaccine (Listorti et al, 2014). They showed that an A rather than T at this position was characteristic of the field strain VC03 being converted to its derived VC03 vaccine (Aviffa/Rhinovax).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the Italian aMPVs subtype B are accumulating progressive mutations from a common progenitor, potentially because of vaccine induced immune pressure (Catelli et al, 2010). Furthermore, the co-presence in the same geographic area of farms housing different avian species sensitive to aMPV, vaccinated with different vaccination programs or not vaccinated (like guinea fowls), and often belonging to the same integrate poultry company, could be a crucial factor for the establishment of an endemic infection (Cecchinato et al, 2013a), reversion to virulence of vaccines and environmental spread of vaccine-derived strains (Catelli et al, 2006;Brown et al, 2011;Cecchinato et al, 2014;Listorti et al, 2014).…”
Section: Discussionmentioning
confidence: 99%